Inflammatory bowel diseases, interleukin-6 and interleukin-6 receptor subunit alpha in causal association with cerebral cortical structure: a Mendelian randomization analysis - Liu, Chunlong; Zhu, Shijie; Zhang, Jian; Ren, Kuiwu; Li, Kangkang; Yu, Jiangtao (Frontiers in Immunology, 2023)
Background: Neurological involvement and psychiatric manifestations have been documented in clinical cases of inflammatory bowel disease (IBD); however, the presence of a causal relationship remains elusive. The objective of this study is to investigate the modifications occurring in the cerebral cortex as a result of IBD. Methods: A compendium of data extracted from a genome-wide association study (GWAS) involving a maximum of 133,380 European subjects. A series of Mendelian random analyses were applied to exclude heterogeneity and pleiotropy, ensuring the stability of the results. Results: Neither IBDs nor inflammatory cytokines (IL-6/ IL-6Rα) were found to have a significant causality with surface area (SA) and thickness (TH) at the global level. At the regional functional brain level, Crohn’s disease (CD) significantly decreased the TH of pars orbitalis (β=-0.003mm, Se=0.001mm, pivw =4.85×10-4). IL-6 was observed to reduce the SA of middle temporal (β=-28.575mm2, Se=6.482mm2, pivw=1.04×10-5) and increase the TH of fusiform (β=0.008mm, Se=0.002mm, pivw=8.86×10-5) and pars opercularis (β=0.009mm, Se=0.002mm, pivw=2.34×10-4). Furthermore, a causal relationship between IL-6Rα and an increase in the SA of superior frontal (β=21.132mm2, Se=5.806mm2, pivw=2.73×10-4) and the TH of supramarginal (β=0.003mm, Se=0.0002mm, pivw=7.86×10-37). All results passed sensitivity analysis and no heterogeneity and pleiotropy were detected. Conclusion: The correlation between IBD and changes in cerebral cortical structures implies the existence of a gut-brain axis at the organismal level. It is recommended that clinical patients with IBD prioritize long-term management of inflammation, as changes at the organismal level can lead to functional pathologies. Magnetic resonance imaging (MRI) may be considered as an additional screening option for IBD.